2015
DOI: 10.1614/wt-d-13-00184.1
|View full text |Cite
|
Sign up to set email alerts
|

Broadleaf Weed Control in Winter-Sown Lentil (Lens culinaris)

Abstract: Winter sowing of lentil results in higher yields than a spring-sown crop. However, when lentil is winter-sown, the critical period of weed control is extended and might require sequential herbicide management strategies to obtain maximum yields. The efficacy of POST alone or soil applied followed by (fb) POST herbicides or hand weeding were evaluated in 2002 and 2003. Trifluralin (PPI) or pendimethalin (PRE) were applied at planting, and pyridate or oxyfluorfen were applied POST at the three- to four-leaf stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…However, PRE applications of pendimethalin and prometryn have been registered to control weeds in lentil in Iran. Karimmojeni et al (2015) found that PRE applications of pendimethalin followed by one hand weeding provided adequate control of broadleaf weeds. Prometryn and linuron also showed satisfactory control on a wide spectrum of weeds in winter-sown lentil .…”
mentioning
confidence: 99%
“…However, PRE applications of pendimethalin and prometryn have been registered to control weeds in lentil in Iran. Karimmojeni et al (2015) found that PRE applications of pendimethalin followed by one hand weeding provided adequate control of broadleaf weeds. Prometryn and linuron also showed satisfactory control on a wide spectrum of weeds in winter-sown lentil .…”
mentioning
confidence: 99%
“…Therefore, the sowing date is another variable that can impact the environmental conditions of weed germination (Singh et al ., 2015). In Mediterranean regions (such as the western parts of Iran), early planting of spring crops late in the winter can prolong the growth period, thereby augmenting the yields (Karimmojeni et al ., 2015). However, in such conditions, weeds can also have early germination, which could in turn cause problems because of the excellent moisture availability early in the growing season.…”
Section: Introductionmentioning
confidence: 99%
“…Karimmojeni et al . (2015) reported that with weed control, winter cultivation of lentils was able to increase its growth period and yield. The seeding rate can also have an effect on weed infestation through rapidly increasing the crop canopy expansion and reducing the incoming light received by weeds (Jha et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations